Investigation Of Spiritual Well-Being Palliative Care Of Patients - Fadime Çinar*, Turgay Sirin (Innovative Journal of Medical and Health Sciences, 2019)
Background: One of the indispensable aspects of the philosophy of holistic care, and negative situations such as life-threatening illness, spiritual well-being, which is defined as the search for a relationship with a divine soul, is a requirement that must be met in order to maintain the existence of the individual. The patient’s need for social and spiritual well-being increases even more in cases of long-term treatment, such as cancer, that reduce the quality of life. Determining and meeting the spiritual needs of the individual in the difficult times of the crisis can be realized by determining the spiritual well-being levels of the individuals and by providing the individual spiritual care. This study was conducted to determine the level of the spiritual well-being of palliative care patients diagnosed with cancer. Methods: This is a descriptive study. The population of the study consisted of 124 patients diagnosed with cancer who were hospitalized in the palliative unit between January and August 2018 and were treated in two state hospitals operating on the European side of Istanbul. The sample consisted of 111 people with voluntary participation and communication. Personal Information Form and Spiritual Well-being Scale were used to collect data. Data were evaluated by one-way analysis of variance (one- way anova) and significance (t-test) of the difference between the two means. Results: The total score averages from the spiritual good scale of individuals participating in the Study were determined to be good with x = 4,15. In terms of the level of education of Scale scores, only "Anomi" is significantly differentiated between groups of age, with a total score of the scale, In the sub-dimension of transcendity and the subdimension of "Harmony with Nature" according to the variable metastasis (p > 0.05). Conclusion: Spiritual Well-being has a positive effect on the healing process of individuals with impaired health. It helps individuals who have a crisis in life threatening diseases such as Cancer to cope with this crisis and to provide spiritual well-being in the sense of life. In This process, spiritual care initiatives by healthcare professionals can be transformed into a part of the healing process and the spiritual goodness of the individual can be increased. Further research in This area is projected to contribute to the richening of the relevant literature in Turkey. Key words: Spiritual, spiritual well-being, palliative care, palliative care unit